Psycholinguistic Perspective on Cognitive Development and Emotional Support in Language Classrooms: Insights from Teachers - Sarwar, Fatima; Fortunasari, Fortunasari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This qualitative study explores the examined intersection of cognitive theory and emotional support in English Foreign Language (EFL) pedagogy by examining how experienced lecturers integrate frameworks like Universal Grammar, the Zone of Proximal Development, and Piagetian stages into their teaching. By linking psycholinguistic theory with classroom practice, the research highlights the combined role of cognitive and emotional scaffolding in supporting second language acquisition. The study aims to understand how theoretical constructs are reflected in practical, real-time classroom instruction, particularly how instructors adapt theory to meet learners’ emotional and cognitive needs. This qualitative research employed a descriptive design and involved nine experienced college-level EFL lecturers from Indonesia, Pakistan, and international settings as the sample. Data were collected through semi-structured interviews focusing on how participants adapt theoretical frameworks to address students’ cognitive and emotional needs in real classroom settings. Semi-structured interviews were conducted with nine college-level lecturers with 10–20 years of experience from Indonesia, Pakistan, and international contexts. The data were analyzed using thematic analysis to identify recurring patterns and core themes related to the integration of theory and practice. In conclusion, the analysis revealed three main findings: lecturers employed implicit scaffolding aligned with theoretical constructs, prioritized emotional safety to support cognitive risk-taking, and faced challenges applying theory across culturally diverse classrooms effective EFL pedagogy.